La Bérénice anglaise de Thomas Otway, ou Racine sans Aristote - Tristan Alonge (Etudes Epistémè)
The article offers an original reassessment of the English adaptation of Racine’s Bérénice by Thomas Otway : Titus and Berenice (1677). It brings out its main novelty, so far rarely explored by critics and yet decisive in explaining the gap in relation to the Racinian text: the role attributed to the character of Antiochus. In a fruitful dialogue between model and imitation, the British “translation” thus presents itself as the revealer that can make visible, by contrast, the latent image of the Racinian text, and that can unveil its secret and transform an “elegant fabric of Madrigals and Elegy” into an Aristotelian tragedy. In Racine’s tragedy, while the story of Titus and Berenice had no tragic characterization and was paradoxically configured as a long and gallant declaration of love constantly postponed, the king of Commagene – a genuine tragic hero – made it possible to reintroduce a tragic progression in the plot. Ignoring the importance of Antiochus, as his contemporary Villars does, Otway chooses to degrade him to the role of rival in love, useless in the course of the action, and must therefore animate his play differently in order to increase the pathos and the twists and turns. In order to meet this challenge, he chooses to radically distort – despite the apparent textual imitations – the characterization of Titus and Berenice, and to exacerbate the destructive and destabilizing effect of amorous passion, to the point of giving the illusion of having written a more Racinian play than Racine himself did.